An appraisal in rule of law terms of the use of policy agendas versus legal norms to protect populations at risk from the global freshwater crisis - Simon Cartaya, Mariana (Kent Law Review, 2018)
This short paper takes an 'international rule of law' perspective in an attempt to weight out policy versus law to solve the normative question of how to best solve the world's freshwater crisis. The issues touching the freshwater crisis have been identified as environmental concerns, human rights concerns, and most prominently, the equitable distribution of natural resources.